2015
DOI: 10.1116/1.4935960
|View full text |Cite
|
Sign up to set email alerts
|

Experimental demonstration of single electron transistors featuring SiO2 plasma-enhanced atomic layer deposition in Ni-SiO2-Ni tunnel junctions

Abstract: We report the use of plasma-enhanced atomic layer deposition (PEALD) to fabricate single-electron transistors (SETs) featuring ultra-thin (≈1 nm) tunnel-transparent SiO2 in Ni-SiO2-Ni tunnel junctions. We show that as a result of the O2 plasma steps in PEALD of SiO2, the top surface of the underlying Ni electrode is oxidized. Additionally, the bottom surface of the upper Ni layer is also oxidized where it is in contact with the deposited SiO2, most likely as a result of oxygen-containing species on the surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
13
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 22 publications
5
13
0
Order By: Relevance
“…Likewise, substituting palladium for nickel on the top layer (Ni-SiO2-Pd) shows behavior indicative of the top palladium layer oxidizing at the metal-SiO2 interface but unlike Al2O3, this oxide can be reduced. These experiments suggest that the oxidation of the top metal layer is unavoidable (at least for oxide dielectrics such as Al2O3 and SiO2) and that reducing the NiO at the This is consistent with hydrogen-promoted reduction of the parasitic NiO to Ni: H 2 + NiO = H 2 O + Ni; the H 2 O is removed during annealing [11,38]. Further measurements of cross-tie devices by TEM and EDX revealed that in addition to the oxide formation on the bottom Ni layer, the top Ni electrodes, deposited on the PEALD SiO 2 , are likewise oxidized and that a second annealing step is required to reduce the parasitic NiO at the lower interface of the top Ni layer [11].…”
Section: Set Devices With Ni-sio 2 -Ni Tunnel Junctionssupporting
confidence: 52%
See 4 more Smart Citations
“…Likewise, substituting palladium for nickel on the top layer (Ni-SiO2-Pd) shows behavior indicative of the top palladium layer oxidizing at the metal-SiO2 interface but unlike Al2O3, this oxide can be reduced. These experiments suggest that the oxidation of the top metal layer is unavoidable (at least for oxide dielectrics such as Al2O3 and SiO2) and that reducing the NiO at the This is consistent with hydrogen-promoted reduction of the parasitic NiO to Ni: H 2 + NiO = H 2 O + Ni; the H 2 O is removed during annealing [11,38]. Further measurements of cross-tie devices by TEM and EDX revealed that in addition to the oxide formation on the bottom Ni layer, the top Ni electrodes, deposited on the PEALD SiO 2 , are likewise oxidized and that a second annealing step is required to reduce the parasitic NiO at the lower interface of the top Ni layer [11].…”
Section: Set Devices With Ni-sio 2 -Ni Tunnel Junctionssupporting
confidence: 52%
“…Fortunately, NiO can be reduced to Ni by annealing in hydrogen at moderately high temperatures ≥300 °C [35][36][37]. We have found that a forming gas anneal (FGA) at 400 °C for 2 min in 5% H2-95% Ar causes the conductance of the cross-tie structures with two cycles of PEALD SiO2 to increase from G ≈ 5 nS to G > 600 μS [11], while a 30 min FGA is required to increase the conductance of the Ni nanowire covered by ~1 nm of SiO2 back to that of the as-deposited nanowires [11,38]. This is consistent with hydrogen-promoted reduction of the parasitic NiO to Ni: H2 + NiO = H2O + Ni; the H2O is removed during annealing [11,38].…”
Section: Set Devices With Ni-sio 2 -Ni Tunnel Junctionsmentioning
confidence: 99%
See 3 more Smart Citations